2015
DOI: 10.1371/journal.pone.0122834
|View full text |Cite
|
Sign up to set email alerts
|

Stable Radical Content and Anti-Radical Activity of Roasted Arabica Coffee: From In-Tact Bean to Coffee Brew

Abstract: The roasting of coffee beans generates stable radicals within melanoidins produced by non-enzymatic browning. Roasting coffee beans has further been suggested to increase the antioxidant (AO) capacity of coffee brews. Herein, we have characterized the radical content and AO capacity of brews prepared from Coffea arabica beans sourced directly from an industrial roasting plant. In-tact beans exhibited electron paramagnetic resonance signals arising from Fe3+, Mn2+ and at least three distinct stable radicals as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…An example of the use of Mn II X-band EPR spectroscopy for the discrimination of Cypriot wines from various grape varieties is shown in Figure 3 (unpublished results). In addition to the characteristic shape of the spectrum, the quantity of Mn II in each wine can be measured from the double-integrated spectra in the presence of standard [14,16] information that can be additionally used as a variable for the wine discrimination.…”
Section: Endogenous Unpaired Electronic Spin Species In Foods 21 Mementioning
confidence: 99%
“…An example of the use of Mn II X-band EPR spectroscopy for the discrimination of Cypriot wines from various grape varieties is shown in Figure 3 (unpublished results). In addition to the characteristic shape of the spectrum, the quantity of Mn II in each wine can be measured from the double-integrated spectra in the presence of standard [14,16] information that can be additionally used as a variable for the wine discrimination.…”
Section: Endogenous Unpaired Electronic Spin Species In Foods 21 Mementioning
confidence: 99%
“…Based from the results presented in Table 1, non-defective green coffee beans had the highest total phenolic compounds to defective green coffee beans and the roasted coffee samples. Troup et al (2015) reported that low molecular weight polyphenolic compounds contributed greatly to the antioxidant activity of coffee brews. In addition, the antioxidant property of green coffee bean extracts is chlorogenic acid (Chachurin et al, 2002;Ramalakshmi et al, 2007;Ramalakshmi et al, 2009;Jeszka-Skowron et al, 2016).…”
Section: Figmentioning
confidence: 99%
“…The metal chelating activity of coffee bean extracts has been attributed to the contribution of low-molecular weight phenolic compounds (Gornas et al, 2016), caffeic acid (Generato-Mattos et al, 2015) and melanoidins (Vignoli et al, 2011;Troup et al, 2015). While metal chelating activity shows an increasing trend relative to the total phenolic compounds in green coffee beans, this was not observed in roasted coffee samples.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The usage of in vitro and in vivo model systems, serve as models for preliminary observations in the evaluation of pharmacological activities, radiation-induced oxidative changes in chemical composition and different EPR spectrum shapes as a function of temperature and time [23,25,26].…”
Section: Introductionmentioning
confidence: 99%